Staining tumor cells with biotinylated ACL-I, a lectin isolated from the marine sponge, Axinella corrugata - Dresch, R. R. (2012)
Axinella corrugata lectin 1 (ACL-1) was purifi ed from aqueous extracts of the marine sponge, Axinella corrugata . ACL-1 strongly agglutinates native rabbit erythrocytes. The hemagglutination is inhibited by N -acetyl derivatives, particularly N , N ’ , N ” -triacetylchitotriose, N -acetyl-Dglucosamine, N -acetyl-D-mannosamine and N -acetyl-D-galactosamine. We investigated the capacity of biotinylated ACL-1 to stain several transformed cell lines including breast (T-47D, MCF7), colon (HT-29), lung (H460), ovary (OVCAR-3) and bladder (T24). ACL-I may bind to both monosaccharides and oligosaccharides of tumor cells, N -acetyl-D-galactosamine, and N -acetyl-Dglucosamine glycan types. The lectins are useful, not only as markers and diagnostic parameters, but also for tissue mapping in suspicious neoplasms. In addition, they provide a better understanding of neoplasms at the cytological and molecular levels. Furthermore, the use of potential metastatic markers such as lectins is crucial for developing successful tools for therapy against cancer. We observed that biotinylated ACL-I stains tumor cells and may hold potential as a probe for identifying transformed cells and for studying glycan structures synthesized by such cells.